The Elements And Impact Of External Quality Assurance On Private Undergraduate Colleges In Yunnan Province, China - Hu, Xiaoling (2024)
External quality assurance has become a pivotal aspect of chinese higher education, as the subject of quality in higher education has gained prominence in china since it is highly related to the prosperity of the economy and the stability of society. It developed very late and is also immature in china, particularly for private undergraduate colleges; the related research is limited. This study is to identify the elements of external quality assurance in private undergraduate colleges, to explore the changes in external quality assurance in private undergraduate colleges, to identify the challenges of external quality assurance in private undergraduate colleges, and to understand the expectations from stakeholders in external quality assurance and private undergraduate colleges. The researcher employed stakeholder theory and governance theories to guide this thesis. With regard to the methodology, the researcher designed the research through a qualitative case study with the guidance of epistemology and social constructive orientation. The interview analysis was utilised as the research instrument. The sample size was 17, six respondents from external quality assurance experts in one evaluation centre, and 11 middle-level leaders from academic affairs offices and employment departments in six private undergraduate colleges. The method also involves triangulation, data collection, data analysis procedures, and ethical consideration. The data was analysed by nvivo 1.71 mac version according to the research questions and sub-questions. It is found that in the first question, there should be various stakeholders in external quality assurance, particularly within the market, which includes third-party agencies, associations, parents, students, the masses, industries, peer colleges, media, public universities, teachers, and international markets.